Zr(IV), La(III), and Ce(IV) Chelates with 2-[(4-[(Z)-1-(2-Hydroxyphenyl)ethylidene]aminobutyl)-ethanimidoyl]phenol: Synthesis, Spectroscopic Characterization, and Antimicrobial Studies. (1st February 2015) - El-ajaily, M. M.; Abdullah, H. A.; Al-janga, Ahmed; Saad, E. E.; Maihub, A. A.
Abstract : La(III), Zr(IV), and Ce(IV) chelates of 2-[(4-[ (Z) -1-(2-hydroxyphenyl)ethylidene]aminobutyl)-ethanimidoyl]phenol were synthesized and characterized by using several physical techniques. The Schiff base was obtained by refluxing of o -hydroxyacetophenone with 1, 4-butanediamine in 2 : 1 molar ratio. The CHN elemental analysis results showed the formation of the Schiff base and the chelates has been found to be in 1 : 1 [M : L] ratio. The molar conductance measurements revealed that all the chelates are nonelectrolytes. Structural elucidations of the ligand and its chelates were based on compatible analytical and spectroscopic evidences. The infrared spectral data revealed that the Schiff base coordinates to the metal ions through active sites which are –OH and –C=N groups. According to the electronic spectral data, an octahedral geometry was proposed for the chelates. The synthesized ligand and its metal chelates were screened for their antimicrobial activity against two Gram negative ( Escherichia coli, Salmonella kentucky ) and two Gram positive ( Lactobacillus fermentum, Streptococcus faecalis ) bacterial strains, unicellular fungi ( Fusarium solani ), and filamentous fungi ( Aspergillus niger ). The activity data showed that the metal chelates have antibacterial and antifungal activity more than the parent Schiff base ligand against one or more bacterial or fungi species. The results also indicated that the metal chelates are higher sensitive antimicrobial agents as compared to the Schiff base ligand.